Turbulent Properties of Internal Waves in the South China Sea - Louis St. Laurent; Harper Simmons; Tswen Yung Tang; YuHuai Wang (Oceanography, 2011)
Luzon Strait and South China Sea waters are among the most energetic internal wave environments in the global ocean. Strong tides and stratification in Luzon Strait give rise to internal waves that propagate west into the South China Sea. The energy carried by the waves is dissipated via turbulent processes. Here, we present and contrast the relatively few direct observations of turbulent dissipation in South China Sea internal waves. Frictional processes active in the bottom boundary layer dissipate some of the energy along China's continental shelf. It appears that more energy is lost in Taiwanese waters of the Dongsha Plateau, where the waves reach their maximum amplitudes, and where the bottom topography abruptly shoals from 3,000 m in the deep basin to 1,000 m and shallower on the plateau. There, energy dissipation by turbulence reaches 1 W m–2, on par with the conversion rates of Luzon Strait.